Nutrient supply rates in a boreal extreme‐rich fen using ion exchange membranes. Issue 7 (22nd June 2018) - Hartsock, Jeremy A.; Bremer, Eric
Abstract: Plant Root Simulator (PRS®) probes have been widely used to assess soil nutrients in the Athabasca Oil Sands Region of northern Alberta, Canada, but their optimum method of use and functionality in natural boreal fens and reclaimed wetlands needs to be determined. A PRS probe consists of an anion or cation exchange resin membrane that is housed in a plastic support. We assessed nutrient adsorption by PRS probes over three incubation periods (2, 24, and 384 hr) in a boreal extreme‐rich fen, a system with moderately high pore water electrical conductivity and a peatland site type that has been targeted in oil sand wetland reclamation. Ion adsorption by PRS probes was similar at 24 and 384 hr for ammonium, nitrate, phosphate, calcium, and magnesium, indicating that a stable or dynamic equilibrium was reached. However, potassium declined from 24 to 384 hr, likely due to displacement by more strongly held cations, while iron and manganese increased, likely due to increasingly anaerobic conditions. The finding that most nutrients were close to equilibrium on PRS probes within 24 hr has important implications for implementation and interpretation of PRS probe data in wetlands with moderately high pore water electrical conductivity.